Investigation of the Predictive Determinants of Social Well-Being in High School Teenagers: An Iranian Study in 2019 - Khatereh Anbari; Javad Tarhani; Seyyed Amir Yasin Ahmadi; Pardis Ghanadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Considering the importance of social well-being and the associated factors, this study wasdesigned to investigate status ofsocial well-being and its predictive determinants in an Iranian group of highschool teenagers during first half of 2019.Methods:An analytical cross-sectional study was conducted on 680 participants. Demographic informationwere collected consisting of age, gender, birth rank, weight, height, economic status of family, education ofparents, place of living and family size. The Persian version of Keyes’s social well-being questionnaire wasused.This questionnaire had parts for social actualization, social coherence, integration, social acceptanceand social contribution.Results: Overall status wise, 13.1% had good status, 80.4% had average status and 6.5% had poor status ofsocial well-being. Urban residency was associated with better score (P=0.036). No significant associationwas observed for age, gender, year of education, having health insurance and birth rank. Educational statusof mother was significantly associated with the overall score in favor of positive association for universityeducation (P=0.046). No significant association was found for father education, mother job and fatherjob. Chronic disorders of the students were associated with decreased overall score (P=0.019). History ofsmoking was associated with decreased overall score (P=0.001). History of regular physical activity wasassociated with increased overall score (P<0.001). No significant association was found for existence ofparental chronic disorder.Conclusion: In the present part of Iran, social well-being has an average status among high school students.Knowing the related factors help us for better planning.